Socs3 expression in myeloid cells modulates the pathogenesis of dextran sulfate sodium (DSS)-induced colitis - Zhou, Lianna; Yan, Zhaoqi; Yang, Wei; Buckley, Jessica A.; Al Diffalha, Sameer; Benveniste, Etty N.; Qin, Hongwei (Frontiers in Immunology, 2023)
Myeloid cells play a critical role in the pathogenesis of Inflammatory Bowel Diseases (IBDs), including Ulcerative Colitis (UC) and Crohn's Disease (CD). Dysregulation of the JAK/STAT pathway is associated with many pathological conditions, including IBD. Suppressors Of Cytokine Signaling (SOCS) are a family of proteins that negatively regulate the JAK/STAT pathway. Our previous studies identified that mice lacking Socs3 in myeloid cells developed a hyper-activated phenotype of macrophages and neutrophils in a pre-clinical model of Multiple Sclerosis. To better understand the function of myeloid cell Socs3 in the pathogenesis of colitis, mice with Socs3 deletion in myeloid cells (Socs3ΔLysM) were utilized in a DSS-induced colitis model. Our results indicate that Socs3 deficiency in myeloid cells leads to more severe colitis induced by DSS, which correlates with increased infiltration of monocytes and neutrophils in the colon and increased numbers of monocytes and neutrophils in the spleen. Furthermore, our results demonstrate that the expression of genes related to the pathogenesis and diagnosis of colitis such as Il1β, Lcn2, S100a8 and S100a9 were specifically enhanced in Socs3-deficient neutrophils localized to the colon and spleen. Conversely, there were no observable differences in gene expression in Ly6C+ monocytes. Depletion of neutrophils using a neutralizing antibody to Ly6G significantly improved the disease severity of DSS-induced colitis in Socs3-deficient mice. Thus, our results suggest that deficiency of Socs3 in myeloid cells exacerbates DSS-induced colitis and that Socs3 prevents overt activation of the immune system in IBD. This study may provide novel therapeutic strategies to IBD patients with hyperactivated neutrophils.